2004
DOI: 10.1111/j.0021-8782.2004.00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐specific expression of the tight junction proteins claudins and occludin in the rat salivary glands

Abstract: Tight junctions (TJs) are essential features of endothelial barrier membranes and of fluid-secreting epithelial cells, such as in the salivary glands. Novel integral membrane proteins have been identified as components of TJs, namely claudins and occludin. The aim of the present study was to determine the distribution of occludin and claudins in the large salivary glands of the rat. The parotid, submandibular and sublingual salivary glands were harvested from adult Sprague-Dawley rats and cryostat sections wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
61
3
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 38 publications
12
61
3
3
Order By: Relevance
“…In these segments, bovine claudin-4 showed distribution both at the TJ and the basolateral membranes. Many investigators have reported basolateral distribution of some claudins, including claudin-4 [1,17,22,23], although the precise roles of claudins in the plasma membrane compartment other than TJ remain unknown; they may simply represent a storage pool capable of being recruited to the TJ when required, or they may have some novel functions in intercellular adhesion and/or adhesion between cells and the extracellular matrix.…”
Section: Claudins Expressed In Tal Of Henle's Loopmentioning
confidence: 99%
“…In these segments, bovine claudin-4 showed distribution both at the TJ and the basolateral membranes. Many investigators have reported basolateral distribution of some claudins, including claudin-4 [1,17,22,23], although the precise roles of claudins in the plasma membrane compartment other than TJ remain unknown; they may simply represent a storage pool capable of being recruited to the TJ when required, or they may have some novel functions in intercellular adhesion and/or adhesion between cells and the extracellular matrix.…”
Section: Claudins Expressed In Tal Of Henle's Loopmentioning
confidence: 99%
“…Previous data showed that a series of tight junction proteins including zonula occludens-1 (ZO-1), occludin, claudin-1, 23, 24 and 25 exist in rat SMG tissue (Peppi and Ghabriel, 2004). Thus, we examined these components in SMG-C6 cells and found that ZO-1, occludin, claudin-1, 23 and 24 mRNA were expressed, whereas claudin-2 and 25 mRNA were not detected (supplementary material Fig.…”
Section: Trpv1 and Occludin Are Expressed In Smg-c6 Cellsmentioning
confidence: 94%
“…It has been reported that, in addition to the aquaporin-5-mediated transcellular transport, the salivation induced by agonists such as carbachol and isoproterenol also involves increased paracellular permeability (Segawa, 1994;Murakami et al, 2001;Hashimoto and Murakami, 2009). To date, occludin has been found in human, rat and mouse major salivary glands (Peppi and Ghabriel, 2004;Kawedia et al, 2007;Lourenço et al, 2007). In murine submandibular gland (SMG) carcinoma cells, the expression of an N-terminally truncated occludin construct causes a decrease in transepithelial electrical resistance (TER) as well as an increase in paracellular permeability (Bamforth et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, Claudin 1 is unexpressed in the luteal endothelial compartment. This is different compared with endothelial cells of the brain and of rat salivary glands (Fujibe et al 2004, Peppi & Ghabriel 2004. In contrast to Claudin 1, Claudin 5 is exclusively localized in the endothelial compartment of the human corpus luteum (Groten et al 2006).…”
Section: Distribution Of Cell Junctional Proteins In the Human Corpusmentioning
confidence: 97%